PHYSIOTHERAPEUTIC TREATMENT AFTER COMPLETE RUPTURE OF THE ANTERIOR CRUCIATE LIGAMENT WITH EMPHASIS ON CLOSED KINETIC CHAIN EXERCISES (CIPEEX, 2024)
&NBSP;PHYSIOTHERAPEUTIC TREATMENT AFTER COMPLETE RUPTURE OF THE ANTERIOR CRUCIATE LIGAMENT WITH EMPHASIS ON CLOSED KINETIC CHAIN EXERCISESINTRODUCTION: THE KNEE IS CONSIDERED TO BE THE MOST COMPLEX JOINT IN THE HUMAN BODY. IT IS A BIAXIAL SYNOVIAL JOINT, I.E., ITS POSITION IS BETWEEN THE FEMUR AND SHINBONE AND BETWEEN THE PATELLA. IT PERFORMS FLEXION, EXTENSION AND MINIMAL ROTATION WHEN FLEXED, AND THERE IS ALSO A CERTAIN AMOUNT OF SLIDING IN THE JOINT. THERE ARE FOUR MAIN LIGAMENTS IN THE KNEE: THE ANTERIOR CRUCIATE LIGAMENT (ACL), THE POSTERIOR CRUCIATE LIGAMENT (PCL), THE LATERAL COLLATERAL LIGAMENT (LCL) AND THE MEDIAL COLLATERAL LIGAMENT (MCL). THE AIM IS TO REPORT ON PHYSIOTHERAPEUTIC INTERVENTIONS, WITH AN EMPHASIS ON CCF MOVEMENTS, IN COMPLETE ACL INJURIES, AND TO DEMONSTRATE THEIR EFFECTIVENESS DURING THE POSTOPERATIVE PERIOD. METHODOLOGY: AN INTEGRATIVE REVIEW WAS CARRIED OUT BY SEARCHING FOR ARTICLES IN THE FOLLOWING VIRTUAL LIBRARIES: PUBMED, GOOGLE SCHOLAR, NETTER, SCIELO, FROM MAY TO SEPTEMBER 2023. THE SEARCH STRATEGY USED THE DESCRIPTORS: ANTERIOR CRUCIATE LIGAMENT (ACL), CLOSED KINETIC CHAIN (CCF), POSTOPERATIVE (PO). RESULTS: THE PREVALENCE OF ACL INJURIES IS SIGNIFICANTLY HIGHER IN WOMEN THAN IN MEN, THREE TO SIX TIMES MORE.&NBSP; CCF EXERCISES ARE AN EFFECTIVE WAY OF PREVENTING ANTERIOR TIBIAL TRANSLATION. CONCLUSION: IT IS THUS CLEAR THAT CLOSED KINETIC CHAIN EXERCISES ARE EFFECTIVE IN ACL RECONSTRUCTION REHABILITATION, PROVIDING RANGE OF MOTION, MUSCLE STRENGTH GAIN, GREATER FUNCTIONALITY AND REDUCED PAIN, AS WELL AS CAUSING LESS LOAD ON THE GRAFT AND ALLOWING A FASTER RETURN TO FUNCTIONAL ACTIVITIES.&NBSP;KEYWORDS:&NBSP; CLOSED KINETIC CHAIN; ANTERIOR CRUCIATE LIGAMENT; POSTOPERATIVE.&NBSP;&NBSP;1STUDENT, EVANGELICAL UNIVERSITY OF GOIS - CAMPUS CERES, E-MAIL: CLEANEANTUNES2303@GMAIL.COM&NBSP;&NBSP;&NBSP;2STUDENT, EVANGELICAL UNIVERSITY OF GOIS - CERES CAMPUS, E-MAIL: FISIO.MA.HENRIQUE@GMAIL.COM&NBSP;&NBSP;3STUDENT, EVANGELICAL UNIVERSITY OF GOIS - CAMPUS CERES, E-MAIL: MIKAELAMR395@GMAIL.COM&NBSP;&NBSP;4STUDENT, EVANGELICAL UNIVERSITY OF GOIS - CAMPUS CERES, E-MAIL: MIKAELB.NUNES@GMAIL.COM&NBSP;&NBSP;5LECTURER, EVANGELICAL UNIVERSITY OF GOIS - CERES CAMPUS, E-MAIL: RENATAFISIO8@HOTMAIL.COM
Keywords: Closed Kinetic Chain; Anterior Cruciate Ligament; Postoperative.